Pengaruh Inovasi Produk Terhadap Keputusan Pembelian Geti Kuda Terbang: (Studi Kasus Di UD. Bu Sulasmi, Kademangan) - Lu’lu Ul Maknunah; Kadela Reka Nur Laili (Universitas Islam Balitar, 2019)
The main problem in this research is how the product innovation affect for purchase decision of Kuda Terbang’s Geti in UD. Mrs. Sulasmi, Kademangan. The purpose of this study is to determine how the product innovation affect for purchase decision of Kuda Terbang’s Geti in UD. Mrs. Sulasmi, Kademangan. Therefore, in order to apply these objectives quantitative methods are used, instrument testing which includes validity tests, reliability tests, assumptions classic tests which include normality tests, and hekteroskedastisitas tests, and hypothesis testing (T-Test). This research activity was carried out in UD. Mrs. Sulasmi is located in Rejowinangun, Kademangan District, Blitar Regency. The results of this study indicate that the calculated T value (0.671) < T table (2.042), while the significance value was 0.507 > 0.05. From the hypothesis that there was a significant influence between product innovation on the purchase decision was rejected (Ha was rejected and Ho was accepted), it means that there was no significant partial effect between product innovation and purchase decision of Kuda Terbang’s geti in UD. Mrs. Sulasmi, Kademangan.